2020
DOI: 10.1002/hlca.202000041
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA‐Binding Protein HuR Is a Kinetically‐Privileged Electrophile Sensor

Abstract: Dedicated to career of and contributions by Prof. Dr. Michael Graetzel (ISIC, EPFL) on his 75 th birthdayThe key mRNA-binding proteins HuR and AUF1 are reported stress sensors in mammals. Intrigued by recent reports of sensitivity of these proteins to the electrophilic lipid prostaglandin A2 and other redox signals, we here examined their sensing abilities to a prototypical redox-linked lipid-derived electrophile, 4-hydroxynonenal (HNE). Leveraging our T-REX electrophile delivery platform, we found that only H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…Signaling changes measured are significantly greater than predicted based on measured occupancy. This result demonstrates that dominant signaling modes occur in redox sensing, and as this has now been shown for several different proteins/pathways (NF-κB 43,51 , PI3K/Akt 43,49,52 , DNA-damage 51 , and antioxidant response 30,31,43,[45][46][47]50 signaling), we cautiously postulate that such behaviors are not uncommon. Such results reconcile some indirect data that had shown that the occupancy on postulated electrophile sensors necessary to trigger signaling was relatively small.…”
Section: Rex Technologies a New Way To Study Electrophile-protein Engagementsupporting
confidence: 63%
See 2 more Smart Citations
“…Signaling changes measured are significantly greater than predicted based on measured occupancy. This result demonstrates that dominant signaling modes occur in redox sensing, and as this has now been shown for several different proteins/pathways (NF-κB 43,51 , PI3K/Akt 43,49,52 , DNA-damage 51 , and antioxidant response 30,31,43,[45][46][47]50 signaling), we cautiously postulate that such behaviors are not uncommon. Such results reconcile some indirect data that had shown that the occupancy on postulated electrophile sensors necessary to trigger signaling was relatively small.…”
Section: Rex Technologies a New Way To Study Electrophile-protein Engagementsupporting
confidence: 63%
“…For several HNE-sensitive proteins, T-REX delivery efficiency (DE) between 15 and 50% triggers signaling phenotypes. 30,31,[44][45][46][47][48][49][50] In several instances the phenotypes stimulated are similar in magnitude to those observed under bolus dosing, or when an inhibitor is used to fully shut down POI activity. Thus, specific electrophile labeling of single proteins is sufficient to trigger signaling.…”
Section: Rex Technologies a New Way To Study Electrophile-protein Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be either inhibitory, or stimulatory, or potentially gain of function 72 . We have identified proteins that sense electrophiles through T-REX TM but do not seem to respond functionally to electrophiles 73 . These for the time being appear to be proteins that are only capable of achieving very low occupancy under standard T-REX TM methods.…”
Section: A Magic Bullet?mentioning
confidence: 99%
“…This article highlights the Aye laboratory research on electrophile signaling and stress response (left panel), wherein precision chemical biology tools are engineered in house aimed at addressing unmet biological questions of significant pharmaceutical relevance. [4,6,9,16,17,[22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43][44] We apply these tools in combination with organic chemistry, biochemistry, and genetic principles in relevant in vivo models illustrated. The figure depicts general concept underlying REX-technologies: Halo-tag-protein covalently bound to photocaged-HNE enables light-driven on-demand delivery of covalent small-molecule such as HNE, Fig.…”
Section: Thetwo Arms Of the Ayelaboratory Researchmentioning
confidence: 99%